Distribution of HAP1-immunoreactive Cells in the Retrosplenial–retrohippocampal Area of Adult Rat Brain and Its Application to a Refined Neuroanatomical Understanding of the Region. (1st December 2018) - Wroblewski, Greggory; Islam, Md. Nabiul; Yanai, Akie; Jahan, Mir Rubayet; Masumoto, Koh-hei; Shinoda, Koh
Highlights: Huntingtin-associated protein 1 (HAP1) immunoreactivity patterns were clarified in retrosplenial–retrohippocampal areas. Five distinct groups of HAP1-immunoreactive cells were identified, particularly in the post-, pre-, and parasubiculum. HAP1 immunoreactivity serves as a highly useful marker in the region. HAP1 may play an important role in preserving these cortical structures and functions for higher nervous activity. Abstract: Huntingtin-associated protein 1 (HAP1) is a neural interactor of huntingtin in Huntington's disease and interacts with gene products in a number of other neurodegenerative diseases. In normal brains, HAP1 is expressed abundantly in the hypothalamus and limbic-associated regions. These areas tend to be spared from neurodegeneration while those with little HAP1 are frequently neurodegenerative targets, suggesting its role as a protective factor against apoptosis. In light of the relationship between neurodegenerative diseases and deterioration of higher nervous activity, it is important to definitively clarify HAP1 expression in a cognitively important brain region, the retrosplenial–retrohippocampal area. Here, HAP1 expression was evaluated immunohistochemically over the retrosplenial cortex, the subicular complex, and the entorhinal and perirhinal cortices. HAP1-immunoreactive (ir) cells were classified into five discrete groups: (1) a distinct retrosplenial cell cluster exclusive to the superficial layers of the granular cortex, (2) a conspicuous, thin line of cells in layers IV/V of the "subiculum-backing cortex, " (3) a group of highly immunoreactive cells associated with the medial entorhinal–subicular corner, (4) pericallosal cells just below layer VI and adjacent to the white matter, and (5) other sporadic, widely-disseminated HAP1-immunoreactive cells. HAP1 was found to be the first marker for the complex subiculum-backing cortex and a precise marker for several subfields in the retrosplenial–retrohippocampal area, verified through comparative staining with other neurochemicals. HAP1 may play an important role in protecting these cortical structures and functions for higher nervous activity by increasing the threshold to neurodegeneration and decreasing vulnerability to stress or aging.